2020
DOI: 10.2196/21698
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Professionals’ Experience of a Digital Tool for Patient Exchange, Anamnesis, and Triage in Primary Care: Qualitative Study

Abstract: Background Despite a growing body of knowledge about eHealth innovations, there is still limited understanding of the implementation of such tools in everyday primary care. Objective The objective of our study was to describe health care staff’s experience with a digital communication system intended for patient-staff encounters via a digital route in primary care. Methods In this qualitative study we conduc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 32 publications
2
47
1
Order By: Relevance
“…A health care organization will have to balance the desire to provide access and simplicity for patients with the obligation to provide healthy and safe working conditions for staff and uphold data privacy, security, and high-quality care ( human-organization ). Compared with the earlier study from our research group regarding the perspectives of HCPs, patients in this study seemed to be somewhat more satisfied with the chat service than the HCPs were [ 4 ]. For example, although anxious to offer patients ample availability, HCPs reported that patients used the chat service to gain quicker access to health care regardless of the degree of urgency of their health problems and sometimes initiated contact for the same complaint through several channels in parallel, which may add to the workload of primary care.…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…A health care organization will have to balance the desire to provide access and simplicity for patients with the obligation to provide healthy and safe working conditions for staff and uphold data privacy, security, and high-quality care ( human-organization ). Compared with the earlier study from our research group regarding the perspectives of HCPs, patients in this study seemed to be somewhat more satisfied with the chat service than the HCPs were [ 4 ]. For example, although anxious to offer patients ample availability, HCPs reported that patients used the chat service to gain quicker access to health care regardless of the degree of urgency of their health problems and sometimes initiated contact for the same complaint through several channels in parallel, which may add to the workload of primary care.…”
Section: Discussioncontrasting
confidence: 72%
“…Both patients in this study and HCPs in the earlier study [ 4 ] regarded the chat as being more on the patients’ terms than traditional face-to-face or telephone communication, although patients, by comparison, seemed to find that as more positive than did the HCPs. Although no earlier interview studies were found with patients regarding modern and fast, primarily mobile phone based, chat services for all inquiries in primary care, there are several studies (both interview and questionnaire studies) regarding patients’ views on other text messaging services in primary care, for inquiries in general, such as in this study, and for the self-management of chronic diseases or health-related interventions, where the patient-professional contact has already been established.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Because innovations in communication technology and clinical data systems are emerging rapidly, there is enormous opportunity. At the same time, substantial uncertainty persists about the consequences of these tools and platforms for the patient care and provider experiences [ 8 , 9 ].…”
Section: Introduction/backgroundmentioning
confidence: 99%